Factors of influence on acute skin toxicity of breast cancer patients treated with standard three-dimensional conformal radiotherapy (3D-CRT) after breast conserving surgery (BCS) - Kraus-Tiefenbacher, Uta; Sfintizky, Andreas; Welzel, Grit; Simeonova-Chergou, Anna; Sperk, Elena; Siebenlist, Kerstin; Mai, Sabine; Wenz, Frederik (Radiation oncology, 2012)
Standard 3D-CRT after BCS may cause skin toxicity with a wide range of intensity including acute effects like erythema or late effects. In order to reduce these side effects it is mandatory to identify potential factors of influence in breast cancer patients undergoing standard three-dimensional conformal radiation therapy (3D-CRT) of the breast and modern systemic therapy.